A vision for global monitoring of biological invasions. (September 2017) - Latombe, Guillaume; Pyšek, Petr; Jeschke, Jonathan M.; Blackburn, Tim M.; Bacher, Sven; Capinha, César; Costello, Mark J.; Fernández, Miguel; Gregory, Richard D.; Hobern, Donald; Hui, Cang; Jetz, Walter; et al.
Abstract: Managing biological invasions relies on good global coverage of species distributions. Accurate information on alien species distributions, obtained from international policy and cross-border co-operation, is required to evaluate trans-boundary and trading partnership risks. However, a standardized approach for systematically monitoring alien species and tracking biological invasions is still lacking. This Perspective presents a vision for global observation and monitoring of biological invasions. We show how the architecture for tracking biological invasions is provided by a minimum information set of Essential Variables, global collaboration on data sharing and infrastructure, and strategic contributions by countries. We show how this novel, synthetic approach to an observation system for alien species provides a tangible and attainable solution to delivering the information needed to slow the rate of new incursions and reduce the impacts of invaders. We identify three Essential Variables for Invasion Monitoring; alien species occurrence, species alien status and alien species impact. We outline how delivery of this minimum information set by joint, complementary contributions from countries and global community initiatives is possible. Country contributions are made feasible using a modular approach where all countries are able to participate and strategically build their contributions to a global information set over time. The vision we outline will deliver wide-ranging benefits to countries and international efforts to slow the rate of biological invasions and minimize their environmental impacts. These benefits will accrue over time as global coverage and information on alien species increases. Graphical abstract: Highlights: Global invasion monitoring is within reach. Tracking biological invasions across scales is key to their management. Essential variables are alien species occurrence, alien status and impact. A modular approach to country monitoring program development is feasible. The approach enables countries with low resourcing and capacity to contribute.